(untitled) (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY STUDIES AND EDUCATION, 2026)
This dissertation examines the prospects for the development of renewable energy sources (RES) in the context of climate change and energy security. The study analyzes the effectiveness of solar and wind energy technologies and the problems of their integration into the general grid. The author substantiates the need to use intelligent technologies to reduce energy losses and ensure system stability. The conclusion contains practical recommendations for accelerating the transition to a green economy.